The association between serum ferritin and blood pressure in adult women: a large cross-sectional study. (18th August 2022) - He, Andong; Yang, Xiaofeng; Ding, Yuzhen; Sun, Lu; Shi, Meiting; Li, Ruiman
ABSTRACT: Background: Studies on the relationships between ferritin and blood pressure remain limited, especially in adult women. The aim of the present study was to investigate the associations between serum ferritin and blood pressure among adult women. Methods: Using the National Health and Nutrition Examination Survey, a cross-sectional study, including 5521 adult women, was performed. Weighted multivariate regressions, subgroup analyses, threshold effect analyses, and sensitivity analysis were used. Results: The authors found that serum ferritin was independently and positively correlated to diastolic blood pressure (DBP), and this positive correlation kept present among women who are 26–30 years old, non-pregnant women, Mexican American women, and women of other races in the subgroup analyses. Additionally, no significant association was found between serum ferritin and systolic blood pressure (SBP), except in women aged 26–30, Mexican American women, and women of other races. In pregnant women, the association between serum ferritin and SBP was an inverted U-shaped curve with an inflection point at 39.5 ng/mL. Conclusions: The authors demonstrated that serum ferritin was positively correlated to DBP in adult women, which may provide a novel reference for clinical management.